Does corporate reputation still affect the cost of equity in an emerging market? Evidence from managerial overconfidence - Nguyen Thi Hoa Hong; Le Thi Thanh Tam (Global Business & Finance Review (GBFR), 2024)
Purpose: This paper examines the relationship between corporate reputation, managerial overconfidence, and the cost of equity in the context of Vietnam - a fast-growing emerging market. Design/methodology/approach: The paper employs Pooled Ordinary Least Square, Fixed Effect Model and Random Effect Model to test the effects of corporate reputation and managerial overconfidence on the cost of equity on 391 non-financial Vietnamese listed firms during 2011 and 2020. In addition, Principal Component Analysis is also applied for calculating the corporate reputation score. Findings: The finding shows that firms with higher corporate reputation are associated with a lower cost of equity. The results also indicates that despite the insignificant relationship between managerial overconfidence and the cost of equity, firms operated by overconfident managers can promote the negative effect between corporate reputa-tion and the cost of equity. In addition, the more reputable corporates increase, the lower the cost of equity will be. Research limitations/implications: Firms in Vietnam can manage the cost of equity better. Furthermore, based on the managers' characteristics and the state of corporate reputation, investors can make appropriate investment decisions. Originality/value: Prior research shows that corporate reputation is negatively related to the implied cost of equity. However, in Vietnamese stock market, under managerial overconfidence, the association between corporate reputa-tion and the cost of equity is also greatly affected. Furthermore, changes in corporate reputation also have certain effects on the cost of equity, especially when corporate reputation is enhanced every year.
Keywords: 650; Corporate reputation; Cost of equity; Emerging market; Managerial overconfidence